ANALYSIS OF STATE-FUNDED TEACHER RECRUITMENT POLICIES: PERSPECTIVES FROM INDONESIA AND MALAYSIA - Fanaturiza, Yopi Agusta; Fauji, Imam; Fahyuni, Eni Fariyatul; Saifudin, Moh; Yusoff, Zuraidah Juliana Mohamad; Sahira, Nabila (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to analyze the teacher recruitment policies of state-salaried teachers in Indonesia and Malaysia, focusing on regulations, selection processes, distribution of placements, and pre-service training systems. Method: The study employs a literature review method with a descriptive-qualitative and comparative approach, analyzing policy documents, academic journals, and official sources from the period 2018–2024. Results: The analysis reveals that Indonesia implements a decentralised recruitment system through the CPNS and PPPK mechanisms, but still faces challenges regarding central-local synchronisation and teacher distribution. Meanwhile, Malaysia adopts a centralized approach with strict selection criteria and an integrated teacher education system. Novelty: In conclusion, Malaysia’s system is more structured, while Indonesia requires strengthened coordination and reform of recruitment management based on regional needs.